BlogNewsRank: Finding and Ranking Frequent News Topics Using Social Media Factors - Harshitha H; Mohammed Rafi (JOIV : International Journal on Informatics Visualization, 2018)
In early days, mass media sources such as news media used to inform us about daily events. Now a days, social media services such as Twitter huge amount of user-generated data, which has a great potential to contain informative news-related content. For these resources to be useful, we have to find a way to filter noise and capture the content that, based on its similarity to the news media, is considered valuable. Even after noise is removed, information overload may still exist in the remaining data. Hence it is convenient to prioritize it for consumption. To achieve prioritization, information must be ranked in order of estimated importance considering mainly three factors. First, the temporal prevalence of a particular topic in the news media is a factor of importance, and can be considered the media focus (MF) of a topic. Second, the temporal prevalence of the topic in social media indicates its user attention (UA). Last, the interaction between the social media users who mention this topic indicates the strength of the community discussing it, and can be regarded as the user interaction (UI) toward the topic. We propose an unsupervised framework—BlogNewsRank—which identiﬁes news topics prevalent in both social media and the news media, and then ranks them by relevance(frequency) using their degrees of MF, UA, and UI.